2011
DOI: 10.1111/j.1525-142x.2011.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and diversification of gene function during mouthpart development in Onthophagus beetles

Abstract: The evolutionary success of insects is in part attributable to the tremendous diversification of their mouthparts, which permitted insects to radiate into novel food niches. The developmental genetic basis of mouthpart development has been well studied in at least two insect taxa possessing derived mouthparts, the hemipteran Oncopeltus fasciatus and Drosophila. However, much less is known about the regulation of mouthpart differentiation of the presumed ancestral mandibulate type. Here we aim to extend current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
4
20
1
Order By: Relevance
“…Embryonic dac expression is weaker in the distal maxillary palp and the labium (Prpic et al 2001). Our data show a clear metamorphic requirement for dac in the intermediate regions of the maxillary and labial palps ( Figure 4D), as does a recent study of O. taurus (Simonnet and Moczek 2011). A function for dac in the development of an intermediate portion of the maxillary and labial appendages has so far been observed only in these two beetles, while data from two species with specialized mouthparts (the milkweed bug Oncopeltus fasciatus and D. melanogaster) showed that dac is not required for PD patterning of the mouthparts (Abzhanov et al 2001;Angelini and Kaufman 2004).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Embryonic dac expression is weaker in the distal maxillary palp and the labium (Prpic et al 2001). Our data show a clear metamorphic requirement for dac in the intermediate regions of the maxillary and labial palps ( Figure 4D), as does a recent study of O. taurus (Simonnet and Moczek 2011). A function for dac in the development of an intermediate portion of the maxillary and labial appendages has so far been observed only in these two beetles, while data from two species with specialized mouthparts (the milkweed bug Oncopeltus fasciatus and D. melanogaster) showed that dac is not required for PD patterning of the mouthparts (Abzhanov et al 2001;Angelini and Kaufman 2004).…”
Section: Discussionsupporting
confidence: 69%
“…Paralleling our results for T. castaneum, in the horned beetle Onthophagus taurus distal regions of the adult mouthparts were deleted with larval Dll RNAi (Simonnet and Moczek 2011). The embryonic and metamorphic functions of Dll in T. castaneum are also similar: the gene is required for the development of distal structures at both stages, and during embryogenesis Dll is expressed throughout the developing palps (Beermann et al 2001).…”
Section: Discussionsupporting
confidence: 68%
“…Most of the recent expression and functional analyses on Dll's role in mandible development collectively suggest that Dll does not play a significant role in the mandibular development of insects (Panganiban et al 1994, Popadic et al 1998, Beermann et al 2001, Angelini & Kaufman 2004, Angelini & Kaufman 2005, Simonnet & Moczek 2011, Coulcher & Telford 2013, and our a priori assumption was that Dll would not be not expressed in stag beetle mandibles. However, it is known that Dll has been independently co-opted during the development of novel traits, especially epidermal outgrowths in insects (Panganiban et al 1994, Moczek & Nagy 2005, Moczek & Rose 2009, Toga et al 2012, raising the possibility that distal patterning, including Dll expression, might have been restored in the evolution of extreme mandible size in these beetles.…”
Section: Distal-less (Dll)mentioning
confidence: 86%
“…One of the defining features of their success is the morphological diversification of appendages, particularly the morphological diversification of mouthparts (Grimaldi & Engel 2005, Simonnet & Moczek 2011. The insect mouthpart ground plan is composed of three paired post-oral appendages known as the labia, maxillae, and mandibles (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation